BIOLOGY LABORATORY WORKSHEET ANALYSIS ON PROTIST MATERIAL - Sa'diatul Fuadiyah; Rahmadhani Fitri; Yosi Laila Rahmi; Defrian Melta; Khalida Ulfa; Dina Rahmawati (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This study aims to analysis and reconstruct student practical worksheets that do not comply with standards. The standard used is the Vee diagram component according to Novak and Gowin (1984). The method used in this research is qualitative descriptive analysis with stages analysis and try it. The sample used was 4 LKP samples from several textbooks used by various Senior High Schools in the city of Padang. The results of the analysis show that the LKP used still has weaknesses, especially in the protist material. The percentage of Vee diagram components that are still lacking is the theory / principle / concept component of 37.5%. Therefore, it is still necessary to develop and perfect practicum worksheets for students to gain concrete knowledge.